Highly Efficient Synthesis and Assay of Protein‐Imprinted Nanogels by Using Magnetic Templates. (15th November 2018) - Mahajan, Rashmi; Rouhi, Mona; Shinde, Sudhirkumar; Bedwell, Thomas; Incel, Anil; Mavliutova, Liliia; Piletsky, Sergey; Nicholls, Ian A.; Sellergren, Börje
Abstract: We report an approach integrating the synthesis of protein‐imprinted nanogels ("plastic antibodies") with a highly sensitive assay employing templates attached to magnetic carriers. The enzymes trypsin and pepsin were immobilized on amino‐functionalized solgel‐coated magnetic nanoparticles (magNPs). Lightly crosslinked fluorescently doped polyacrylamide nanogels were subsequently produced by high‐dilution polymerization of monomers in the presence of the magNPs. The nanogels were characterised by a novel competitive fluorescence assay employing identical protein‐conjugated nanoparticles as ligands to reversibly immobilize the corresponding nanogels. Both nanogels exhibited K d <10 pM for their respective target protein and low cross‐reactivity with five reference proteins. This agrees with affinities reported for solid‐phase‐synthesized nanogels prepared using low‐surface‐area glass‐bead supports. This approach simplifies the development and production of plastic antibodies and offers direct access to a practical bioassay.